A Bracket-Stiffened Two-Planar Overlapped Tubular KT-Joint for Offshore Jack-Up Fatigue Analysis - Jian Zhang; Xinxin Yue; Jiajia Qiu; Lei Chen; Wei Shen (Advances in Civil Engineering)
There have been a large number of research programs dedicated to the investigation of stress concentration factor and its parametric design formulae for a variety of uniplanar and multiplanar tubular joints. However, for the multiplanar overlapped tubular joints, the related reports are very limited due to the fact that the combining effect between multiplanarity and brace overlapping is quite complex. In this paper, a novel bracket-stiffened two-planar overlapped tubular KT-joint is proposed by adding two brackets between the upper diagonal and horizontal braces to alleviate the stress concentration at the brace-to-chord intersection area. As compared with the original KT-joint and KT-joint of larger brace gap, stress concentration reduction and fatigue strength enhancement at the most critical point of the proposed KT-joint are significant under both axial and in-plane bending (IPB) loads. The superiority of the proposed KT-joint is further tested with a simplified fatigue life assessment of offshore jack-up in field transit condition, when the KT-joint corresponding to the upper guide level is most critical and fatigue-sensitive. The obtained results with conservative assumptions may serve as guides or references in civil and offshore engineering practices.